Education under attack: Teachers’ perspectives on the effects of anglophone crises on secondary schools: Implications for Cameroon’s educational development - Awu, Isaac Oben; Hui, Xu (Journal of Education, Health and Sport, 2025)
The ongoing Anglophone Crisis has severely affected Cameroon’s education system, with over 80% of schools closed, disrupting the educational trajectory of an entire generation, denying more than 600,000 children access and right to education in the Northwest and Southwest regions. This study explored teachers’ perspectives on the effects of the Anglophone Crisis on secondary schools in Cameroon’s Northwest and Southwest regions. The study employed a qualitative research methodology. The participants were 27 teachers from 12 Cameroon secondary schools. A purposive sampling technique was used to select the participants; only secondary school teachers who are still actively involved in teaching and residing in Cameroon’s Northwest and Southwest regions participated in the study. A semi-structured interview guide was used as the instrument for data collection. The data was analyzed thematically. The study found that the ongoing anglophone crisis has affected secondary schools in several ways, including (1) damaged educational infrastructure (2) teacher shortages and professional challenges (3) disrupted learning continuity (4) students displacement (5) psychological impact on students. We, contend that the ongoing Anglophone crisis in Cameroon has profound impact for schooling and with long-term implications for educational development, quality and broader societal progress in areas such as; human rights violation; student/teachers well being, exacerbated inequalities, peace-building, poverty reduction, human development, social cohesion and economic growth etc. Addressing these challenges is essential for restoring and enhancing the quality of education in the affected regions. The study emphasizes the need for targeted interventions that consider the unique context of the Anglophone Crisis, aside resonating with other affected areas across the globe.